PEMILIHAN MODEL CO-MANAGEMENT PENGELOLAAN PERIKANAN TANGKAP - Sutomo Sutomo; Ari Purbayanto; Domu Simbolon; Mustaruddin Manan (Fakultas Perikanan dan Ilmu Kelautan, 2011)
Option of Co-management model of fisheries management in pelabuhanratu, sukabumi regency, west java is largely determined by the criteria / management aspect to be achieved, the management of conditions that exist today, and alternative co-management model is offered in the management of capture fisheries. Election of co-management model of fisheries management in study area is also influenced by a variety of obstacles / barries. This study aims to formulate a model selections Fisheries co-management in pelabuhanratu catch. This study uses the AHP method. Several significant interaction management components are (a) The biological aspects of the firts order of the ratio of interest RK = 0.346 to IR =0.07. (b) The economic aspects of the sequence in two, namely the ratio of interest RK = 0.286 to IR= 0.07 (c) Social aspects that is associated whit a third order RK = 0.25 at IR = 0.07.